The questioning of the rational in the prose of the fin de siècle from a Latin American and Central European perspective - Poláková, Dora (Anales de Literatura Hispanoamericana, 2021)
The article focuses on the ambiguous position that the artists of the fin de siècle adopt in the face of the worship of rational knowledge. It shows how artists highlight other levels of reality in their works; the fantastic, the mysterious, the weird. This view is common to Hispanic modernists and Czech authors even if they live and write in different historical and social contexts.
Keywords: modernism; fin de siècle; prose; fantastic; enigma; Darío; Karásek